China's remarkable economic growth - Knight, John B. 1939-; Ding, Sai 1969- (Oxford University Press, 2012)
China's economy has been growing at 10% per annum for the last three decades. This book considers one of the biggest questions facing contemporary economists: why and how is the Chinese economy growing so fast?